Do Water-aided Techniques Improve Serrated Polyp Detection Rate During Colonoscopy?: A Systematic Review With Meta-Analysis. Issue 6 (July 2021) - Aziz, Muhammad; Mehta, Tej I.; Weissman, Simcha; Sharma, Sachit; Fatima, Rawish; Khan, Zubair; Dasari, Chandra S.; Lee-Smith, Wade; Nawras, Ali; Adler, Douglas G.
Abstract : Background and Study Aims: The utility of water-aided techniques (WT): water exchange (WE) and water immersion (WI) have been studied extensively in the literature for improving colonoscopy outcome metrics such as adenoma detection rate. Serrated polyps owing to their location and appearance have a high miss rate. The authors performed a systematic review and meta-analysis of studies comparing WT with the standard gas-assisted (GA) method to determine if there was any impact on serrated polyp detection rate (SPDR) and sessile serrated polyp detection rate. Methods: The following databases were queried for this systematic review: Medline, EMBASE, Cochrane Library, CINAHL, and Web of Sciences. The authors only included randomized controlled trials (RCTs). The primary outcome was SPDR and secondary outcomes were sessile serrated polyp detection rate and cecal intubation rate. Risk ratios (RRs) were calculated for each outcome. A P -value <0.05 was considered to be statistically significant. Results: A total of 4 RCTs (5 arms) with 5306 patients (2571 in the GA group and 2735 in the WT group) were included. The SPDR was significantly increased for the WT group compared with GA (6.1% vs. 3.8%; RR, 1.63; 95% confidence interval, 1.24-2.13; P <0.001; I 2 =22.7%). A subgroup analysis for WE technique also demonstrated improved SPDR compared with the GA method (4.9% vs. 3.2%; RR, 1.57; 95% confidence interval, 1.15-2.14; P =0.004; I 2 =6.1%). Conclusions: WT, particularly, the WE method results in improved SPDR. This technique should be encouraged in a clinical setting to detect these polyps to prevent interval colorectal cancer. Abstract : Supplemental Digital Content is available in the text.